Drama/Tragedy - Hollins, Martha; Guidance Associates (Australia : Contemporary Arts Media)
This program explores the major aspects of character and structure in tragis drama. The tragis world, tragic conflict and the tragis hero are illustrated and explored through selection from such great dramatists as Tennessee Williams, Chekhov, ibsen, Shakespeare, O'Neill, Sopocles and Arthur Miller. Throughout, the program refers to Aristotle's insights into the natute of tragedy
Title from container
DVD format
Keywords: Tragedy -- History and criticism; Drama -- History and criticism; Literary form